2020
DOI: 10.26656/fr.2017.4(s4).003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enzymatic hydrolysis on the antioxidant activities and amino acid profiles of defatted chia (Salvia hispanica L.) flour

Abstract: The aim of this study was to determine the effect of enzymatic hydrolysis using different proteases (Alcalase® and papain) and hydrolysis period on antioxidative activities and amino acid profiles of hydrolysed chia peptides. The experiment has been carried out using a completely randomized block design. The protein from defatted chia flour (DCF) was first isolated using different extraction pH (pH 10; 11; 12) and precipitation pH (pH 3.5, 4.0 and 4.5) to determine the highest protein isolated (CI) yield. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…At this point, surface hydrophobicity increased with further increases in temperature ( Figure 1F ). Interestingly, hydrolysis time showed a similar tendency to surface hydrophobicity, with the lowest value at a hydrolysis time of about 3.6–4.4 h. This could be due to the exposure or burial of the hydrophobic amino acid residues, which changed with the progression of enzymatic hydrolysis ( 14 ).…”
Section: Resultsmentioning
confidence: 97%
“…At this point, surface hydrophobicity increased with further increases in temperature ( Figure 1F ). Interestingly, hydrolysis time showed a similar tendency to surface hydrophobicity, with the lowest value at a hydrolysis time of about 3.6–4.4 h. This could be due to the exposure or burial of the hydrophobic amino acid residues, which changed with the progression of enzymatic hydrolysis ( 14 ).…”
Section: Resultsmentioning
confidence: 97%
“…According to SDS-PAGE patterns of hydrolysates viz., A₅ to A₃₀ showed that the Alcalase effectively cleaved proteins in hydrolysates and size was significantly reduced with the increase in reaction time. During the initial hydrolysis stage, both enzyme activity and substrate concentration were comparatively higher, resulting in the breakdown of peptide bonds and proteolysis occurring at higher rates [ 13 ]. This may lead to the initial increase in DPPH free radical scavenging capacity, and then further interactions of peptides or functional groups of amino acids may reduce DPPH values.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, complexes between phenolics and proteins may affect the bio-accessibility and bioavailability of proteins and phenolics by protecting them from oxidizing as they pass through the GI tract [ 11 ]. To improve the bioavailability of phenolics and protein digestibility, protein hydrolysis may be commercially implemented by using protease enzymes such as Alcalase to help decompose protein into smaller peptides and free amino acids, thereby promoting antioxidant capacity [ 12 , 13 ]. Several processing techniques (such as ultra-high temperature processing, high shear strength mixing, and homogenization) also assist in enhancing the stability of protein emulsions by generating pressure and heating impacts [ 14 ], which further provide specific antioxidant potential due to the formation of some Maillard reaction products [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the production of low Phe protein hydrolysates (LPHs) is usually based on a two-step approach: (i) Phe is released by the enzymatic hydrolysis of the protein and (ii) Phe residues are removed by ultrafiltration, gel chromatography or adsorption (Su et al 2021a). Enzymatic hydrolysis is a common method of releasing amino acids from proteins, while deep hydrolysis can release more amino acids and produce large amounts of oligopeptides (Ibrahim and Ghani 2020). Compared to the other two methods for Phe removal, adsorption is a more effective post-treatment way because it maximises the retention of low molecular weight nutrients (such as amino acids and oligopeptides) and is inexpensive (Lopes et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…2021a). Enzymatic hydrolysis is a common method of releasing amino acids from proteins, while deep hydrolysis can release more amino acids and produce large amounts of oligopeptides (Ibrahim and Ghani 2020). Compared to the other two methods for Phe removal, adsorption is a more effective post‐treatment way because it maximises the retention of low molecular weight nutrients (such as amino acids and oligopeptides) and is inexpensive (Lopes et al.…”
Section: Introductionmentioning
confidence: 99%